Comparative Mitogenomics of Clitellata Reveals Mitogenome Organization Can Affect the Mode of Phylogeny - Mercan, Deni̇z; Horenkamp, Austin; Aydemi̇r, Merve Nur; Aydemi̇r, Habeş Bi̇lal; Neubig, Kurt; Arslan, Nai̇me; Anderson, Frank E (The Scientific and Technological Research Council of Turkey, 2025)
Clitellata is a major clade of Annelida that includes almost all freshwater and terrestrial annelids as well as many marine species. Aquatic oligochaetes include the union of the two multispecies families: Naididae and Tubificidae. There has been much debate regarding the phylogeny and classification of the cosmopolitan and diverse Naididae. In this study, the total mitogenome sequences of Potamothrix hammoniensis (Naididae: Tubificinae), Stylaria fossularis, Stylaria lacustris, Chaetogaster diaphanus, Chaetogaster diaphanus sp. B, and Slavina appendiculata (Naididae: Naidinae) were sequenced and characterized and can be accessed from NCBI under accession numbers OQ654101, PP909790, PP909791, PP909792, PP909793, and PP893275, respectively. For comparative analysis, 101 clitellate mitogenome sequences (from 70 oligochaetes and 31 hirudineans) were downloaded from NCBI. Comparative analysis showed that nine anticodon-codon interactions do not have exact matches—a pattern consistent with the restriction of transcription by mito-tRNAs. Within Clitellata, nine different gene order patterns were determined, and four of them were found in Naididae. This suggests that mitochondrial gene order shows a cumulative effect in the evolution of mitogenome sequences. Based on phylogenetic analysis, it appears that stronger support for Clitellata can be achieved with additional sequences. Additional sequences sampled from several other families could be used for even more stability.
Keywords: 31 Biological Sciences; 3104 Evolutionary Biology; 0608 Zoology; 3109 Zoology; Comparative mitogenomics; mtDNA; Clitellata phylogeny; Naididae